Magnetite nanoparticles coated with PEG 3350-tween 80: In vitro characterization using primary cell cultures - Chapa, Christian (2020)
Some medical applications of magnetic nanoparticles require direct contact with healthy tissues and blood. If nanoparticles are not designed properly, they can cause several problems, such as cytotoxicity or hemolysis. A strategy for improvement the biological proprieties of magnetic nanoparticles is their functionalization with biocompatible polymers and nonionic surfactants. In this study we compared bare magnetite nanoparticles against magnetite nanoparticles coated with a combination of polyethylene glycol 3350 (PEG 3350) and polysorbate 80 (Tween 80). Physical characteristics of nanoparticles were evaluated. A primary culture of sheep adipose mesenchymal stem cells was developed to measure nanoparticle cytotoxicity. A sample of erythrocytes from a healthy donor was used for the hemolysis assay. Results showed the successful obtention of magnetite nanoparticles coated with PEG 3350-Tween 80, with a spherical shape, average size of 119.2 nm and a zeta potential of +5.61 mV. Interaction with mesenchymal stem cells showed a non-cytotoxic propriety at doses lower than 1000 µg/mL. Interaction with erythrocytes showed a non-hemolytic propriety at doses lower than 100 µg/mL. In vitro information obtained from this work concludes that the use of magnetite nanoparticles coated with PEG 3350-Tween 80 is safe for a biological system at low doses.